Beating Heart Coronary Artery Bypass Grafting with Preemptive Impella™ 5.5 Assist Device in Ischemic Cardiomyopathy - Francesco Cabrucci; Massimo Baudo; Yoshiyuki Yamashita; Amanda Yakobitis; Courtney Murray; Gianluca Torregrossa (Biomedicines)
Background: Choosing the best surgical approach for coronary revascularization in patients with ischemic cardiomyopathy and low EF is complex. Several strategies have been adopted, including on- and off-pump CABG, the use of IABP, and the combination of ECMO or even LVAD with CABG. Recently, the Impella 5.5 micro-axial pump has been used as perioperative temporary left ventricular support in CABG patients. This study aims to report a series of CABG procedures performed with Impella assistance, highlighting its potential benefits in high-risk surgery cases. Methods: Between January 2023 and December 2024, seven consecutive patients underwent on-pump beating CABG with planned central Impella 5.5 support via a 10 mm graft in the ascending aorta. This study focused on assessing perioperative outcomes in patients with reduced ventricular dysfunction (ejection fraction [EF] < 35%) undergoing CABG with Impella-assisted support. Results: Seven patients were included in the study, with a median age of 70 [IQR 57–74.7], and six were male. Hypertension was present in all patients, diabetes in six, and COPD in two, and two were in dialysis. The median preoperative EF was 20% [IQR, 18–29%], and the median STS PROM was 5.5 [IQR: 2.9–8.9]. One patient had preoperative IABP support. Four patients required intraoperative transfusions, but all remained hemodynamically stable upon OR exit. The Impella was removed after an average of 5.6 ± 2.1 days. One patient underwent surgical revision for bleeding. No strokes, myocardial infarctions, repeat revascularizations, or mortality occurred postoperatively. The median postoperative hospital stay was 21 [IQR, 17.5–22] days, with a discharge EF of 38% [IQR 33.5–38%]. One patient died 6 months after the procedure due to sepsis caused by a gangrenous diabetic leg. Conclusions: This initial experience using Impella 5.5 support in CABG patients with reduced EF demonstrated its feasibility in selected cases. The Impella provided effective circulatory support, ensuring stable hemodynamics throughout the postoperative stay without complications.